The Causes and Effects of Quality of Brand Relationship and Customer Engagement - Zain Noori Ismael (International Journal of Humanities and Education Development (IJHED), 2022)
In order to validate this study, the researchers turned to a quantitative methodology. There were a total of 140 questionnaires handed out at the various private companies; however, only 128 of those questionnaires were returned, and only 128 of those were correctly filled out. The data was obtained through the use of hard copies. The findings demonstrated a significant and positive relationship between quality of brand relationship and customer engagement at selected private businesses in Kurdistan. The findings of this study will be beneficial for the field of culture studies, for example, culture diversification and its relationship with the quality of brand relationships. Furthermore, the researchers suggested that further studies be conducted in the field of cultural issues and the relationship quality of brand relationships to determine whether or not culture will have an effect on accepting certain customer engagement.